The Exemplary Life of Dimitrios Vikelas (1835-1908) - Smith, Michael Llewellyn (The Historical Review/La Revue Historique, 2007)
This paper describes the "satisfying curve" of Dimitrios Vikelas’ life journey, starting from Syros in 1835, moving via Constantinople, Odessa, and Syros again, to London, Paris and finally Athens. It explores Vikelas’ multiple aspects, as merchant, writer, traveller, lecturer and essayist, Olympic founder, educationalist, book collector and philanthropist, all of which were united in the public-spirited man of letters (logios). It sets Vikelas in the context of the Greek commercial diaspora, the world of the London expatriate Greek community, and the dynamic society of late nineteenth-century Athens, beginning in the 1870s to act as a magnet to Greek expatriates. The author stresses two qualities of Vikelas: his belief in the idea of a progressive Greek state marked by advances in education, culture, tourism and standards of public life; and the self-awareness and experience which inform his autobiographical writings, not only his memoir My Life but also his last such work, The War of 1897.